2021
DOI: 10.3390/sports9070093
|View full text |Cite
|
Sign up to set email alerts
|

Sprint and Jump Mechanical Profiles in Academy Rugby League Players: Positional Differences and the Associations between Profiles and Sprint Performance

Abstract: This cross-sectional study evaluated the sprint and jump mechanical profiles of male academy rugby league players, the differences between positions, and the associations between mechanical profiles and sprint performance. Twenty academy rugby league players performed 40-m sprints and squat jumps at increasing loads (0–80 kg) to determine individual mechanical (force-velocity-power) and performance variables. The mechanical variables (absolute and relative theoretical maximal force-velocity-power, force-veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(140 reference statements)
0
4
0
Order By: Relevance
“…Samozino et al [52] recently identified acceleration performance less than 30m largely depends on P MAX and individual mechanical characteristics, further identifying the necessity to develop and express this mechanical quality to be an effective field hockey player. These findings have been supported in similar studies, but not all (r = 0.27) [53] involving amateur netball players, academy rugby players, high-level sprint athletes and professionl male and female football players, (r = 0.40−0.75) [14,[18][19][20], further highlighting the need for power development expression in field and court sports. However, across these studies, most force variables (F 0 ) did not achieve significance (r ≤ 0.27), thereby demonstrating a greater emphasis on movement velocity capabilities to express maximal external power.…”
Section: Discussionmentioning
confidence: 54%
“…Samozino et al [52] recently identified acceleration performance less than 30m largely depends on P MAX and individual mechanical characteristics, further identifying the necessity to develop and express this mechanical quality to be an effective field hockey player. These findings have been supported in similar studies, but not all (r = 0.27) [53] involving amateur netball players, academy rugby players, high-level sprint athletes and professionl male and female football players, (r = 0.40−0.75) [14,[18][19][20], further highlighting the need for power development expression in field and court sports. However, across these studies, most force variables (F 0 ) did not achieve significance (r ≤ 0.27), thereby demonstrating a greater emphasis on movement velocity capabilities to express maximal external power.…”
Section: Discussionmentioning
confidence: 54%
“…The absence of any condition in the present investigation in which jump momentum was a stronger predictor of sprint momentum than using body mass alone further reinforces the apparent lack of evidence to support using jump momentum for this purpose over other alternatives in applied settings. Furthermore, the correlations between body mass and sprint momentum ( r = 0.97 [CI: 0.97, 0.98]) were greater than those recently reported between sprint momentum and any jump or sprint force‐velocity profile parameter (greatest r = 0.88 for sprint theoretical maximal horizontal force; Nicholson et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
“…body mass or sprint velocity). Due to the challenging and potentially fatiguing nature of regular sprint momentum assessment, there may be a benefit to researchers and practitioners from alternative jump‐based tests to predict sprint momentum (Agar‐Newman & Klimstra, 2015; Harry et al, 2021; Jalilvand, Banoocy, Rumpf, & Lockie, 2019; McMahon, Lake, Ripley, & Comfort, 2020; Nicholson, Dinsdale, Jones, & Till, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The vertical force-velocity profile (FVP) meets the requirements of specificity and individualization since it visualizes, by vertical jump performance, the strong relationship between the force applied by a subject and the velocity at which the subject applies that force per unit time (RFD) [15,[21][22][23][24], thus establishing individualized imbalances, either force or velocity [25], that will guide the intervention program until the optimization of the vertical force-velocity profile is achieved. The vertical force-velocity profile has been used and contrasted in the high performance of collective sports: basketball [26], soccer [27], handball [24], rugby [28] and water polo [29], among others. It has even been tested in young soccer players in training [30], but not in basketball players at maturing age.…”
Section: Introductionmentioning
confidence: 99%